The acceptability of compassion-focused therapy in clinical populations: a metasynthesis of the qualitative literature - Garrett, Charlotte; Smith, Debbie M.; Wittkowski, Anja (Frontiers in Psychiatry, 2025)
BackgroundCompassion-focused therapy (CFT) is a psychological intervention that is increasingly used in UK NHS services, either in an individual or a group format, with individuals experiencing psychological difficulties. Reviews of the quantitative evidence suggest that CFT effectively improves psychological well-being in various clinical groups. Participant experiences of group CFT in those with psychological difficulties have also been explored in several published qualitative and mixed-methods studies. Thus, the aim of this review was to further our understanding of the acceptability of group CFT, in relation to both the content of the intervention and its delivery, in order to help inform the future design and delivery of CFT in clinical services.MethodFollowing the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines, eight relevant databases were searched for terms associated with CFT and qualitative research. The methodological quality of included studies was appraised using the Critical Appraisal Skills Programme (CASP) screening tool. Findings were synthesised using thematic synthesis.ResultsTwelve studies involving 106 participants with psychological difficulties met inclusion criteria. Five main themes were developed from the extracted data: 1) participants’ experiences prior to the intervention, 2) initial response to the idea of participation, 3) participants’ experiences of the intervention: aspects valued or considered beneficial, 4) valued outcomes of the intervention, and 5) the end of the intervention and moving forward.ConclusionsFindings indicated a high level of acceptability of group CFT and commonality of experiences across participants despite different clinical presentations. The crucial role played by facilitators and other group members to participant engagement and outcomes was highlighted, among other factors. Clinical and research implications of these findings are discussed.